2018
DOI: 10.5205/1981-8963-v12i2a234689p465-474-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, antimicrobial and healing activity of the Jatropha gossypiifolia L extract.

Abstract: RESUMOObjetivo: investigar o potencial citotóxico, antimicrobiano e cicatrizante de extratos das folhas, galhos e caule da J. gossypiifolia L. Método: estudo quantitativo, experimental. Os extratos foram obtidos por maceração em etanol, concentrados em evaporador rotatório e secos em dessecador a vácuo. Na análise, realizaram-se testes de prospecção fitoquímica; citotoxidade; microdiluição em caldo e Scratch assay. Entre os metabólitos detectados, estiveram: taninos, esteroides, flavonoides, flavonas, xantonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This plant exhibited significant antiinflammatory power with a decrease in edema, nitric oxide production, myeloperoxidase enzyme and oxidative stress, with an intensity similar to dexamethasone, and this plant may have the ability to inhibit the migration of neutrophils and pro-inflammatory mediators such as histamine, serotonin, bradykinin and prostaglandins. Silva et al (2018) proved that the methanolic extracts of the leaves of J. gossypiifolia L. have healing power, with a 45% increase in fibroblasts in an in vitro test, which observed cell proliferation at zero, 12 and 24 hours and concluded that this species may be a wound healing herbal alternative, but further studies are needed.…”
Section: Resultsmentioning
confidence: 99%
“…This plant exhibited significant antiinflammatory power with a decrease in edema, nitric oxide production, myeloperoxidase enzyme and oxidative stress, with an intensity similar to dexamethasone, and this plant may have the ability to inhibit the migration of neutrophils and pro-inflammatory mediators such as histamine, serotonin, bradykinin and prostaglandins. Silva et al (2018) proved that the methanolic extracts of the leaves of J. gossypiifolia L. have healing power, with a 45% increase in fibroblasts in an in vitro test, which observed cell proliferation at zero, 12 and 24 hours and concluded that this species may be a wound healing herbal alternative, but further studies are needed.…”
Section: Resultsmentioning
confidence: 99%